2021
DOI: 10.3390/ijerph18147429
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Greenness Exposure and IQ-Associated DNA Methylation: A Prospective Cohort Study

Abstract: Epigenetics is known to be involved in regulatory pathways through which greenness exposure influences child development and health. We aimed to investigate the associations between residential surrounding greenness and DNA methylation changes in children, and further assessed the association between DNA methylation and children’s intelligence quotient (IQ) in a prospective cohort study. We identified cytosine-guanine dinucleotide sites (CpGs) associated with cognitive abilities from epigenome- and genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…[1][2][3] However, as described by the hypothesis of Developmental Origins of Health and Diseases" (DoHaD), some of these observed associations could already originate during fetal development [4][5][6][7] , which is considered an important phase in which the brain develops and neurocognitive maturation takes place. [8,9] A proposed way through which green space could influence child (neuro)development is by affecting epigenetic mechanisms [10,11] , such as DNA methylation, thereby shaping early-life conditions and development. [12][13][14] For example, a recent study by Lee et al (2021) provided evidence for an association between residential green space and cognitive ability-related DNA methylation in children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] However, as described by the hypothesis of Developmental Origins of Health and Diseases" (DoHaD), some of these observed associations could already originate during fetal development [4][5][6][7] , which is considered an important phase in which the brain develops and neurocognitive maturation takes place. [8,9] A proposed way through which green space could influence child (neuro)development is by affecting epigenetic mechanisms [10,11] , such as DNA methylation, thereby shaping early-life conditions and development. [12][13][14] For example, a recent study by Lee et al (2021) provided evidence for an association between residential green space and cognitive ability-related DNA methylation in children.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] A proposed way through which green space could influence child (neuro)development is by affecting epigenetic mechanisms [10,11] , such as DNA methylation, thereby shaping early-life conditions and development. [12][13][14] For example, a recent study by Lee et al (2021) provided evidence for an association between residential green space and cognitive ability-related DNA methylation in children. [10] Given this knowledge it is particularly interesting to investigate the epigenetics that take place within the placenta, as they can be readily influenced by the maternal environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, long-term exposure to green space was associated with a decreased risk of childhood-associated behavioral problems concerning emotion, conduct and hyperactivity ( Amoly et al, 2014 , Bijnens et al, 2020 , Markevych et al, 2014 ) and associated with a lower risk of psychiatric disorders as found in a large-scale study covering more than 900,000 Danish individuals ( Engemann et al, 2019 ). Additionally, studies found that children residing in an environment surrounded with more green could better memorize, were more attentive and had a higher intelligence quotient ( Bijnens et al, 2020 , Dadvand et al, 2017 , Lee et al, 2021 ). However, most studies investigating cognitive function and green space examined school-aged children aged six to 12, whereas observable differences in cognitive capabilities are already present at the preschool age, which is an important developmental stage in children ( National Research et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%